New information from Maszycka Cave and the Late Glacial recolonisation of Central Europe - Kozłowski, Stefan Karol; Połtowicz-Bobak, Marta; Bobak, Dariusz; Terberger, Thomas (Elsevier, 2012)
Maszycka cave is one of the most important Magdalenian sites in Central Europe. The assemblage is characterized by a considerable number of organic tools including points, navettes and a decorated perforated antler. The cave was related to the middle Magdalenian of western Europe and identified as one of the earliest Magdalenian sites of Central Europe. A series of four AMS-dates now assigns the site more precisely to the period 16,350 to 16,100 calBC (c. 15.000 BP). No other reliably dated Magdalenian sites of this early period of recolonisation of southern Central Europe are known and its clearest parallels to the west are the Grotte Grappin at Arlay in western France and perhaps the open air site Munzingen in southwestern Germany. After the first short episode of recolonisation, a more permanent Magdalenian expansion into Central Europe started hundreds of years later with sites such as Kesslerloch in northern Switzerland.
Keywords: Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::Archaeology subjects::Archaeology; Magdalenian; Maszycka Cave; navette; Upper Palaeolithic; Southern Poland